Inhibition of NK1.1 signaling attenuates pressure overload-induced heart failure, and consequent pulmonary inflammation and remodeling - He, Xiaochen; Xu, Rui; Pan, Lihong; Bhattarai, Umesh; Liu, Xiaoguang; Zeng, Heng; Chen, Jian-Xiong; Hall, Michael E.; Chen, Yingjie (Frontiers in Immunology, 2023)
Background: Inflammation contributes to heart failure (HF) development, the progression from left ventricular failure to pulmonary remodeling, and the consequent right ventricular hypertrophy and failure. NK1.1 plays a critical role in Natural killer (NK) and NK T (NKT) cells, but the role of NK1.1 in HF development and progression is unknown. Methods: We studied the effects of NK1.1 inhibition on transverse aortic constriction (TAC)induced cardiopulmonary inflammation, HF development, and HF progression in immunocompetent male mice of C57BL/6J background. Results: We found that NK1.1 + cell-derived interferon gamma + (IFN-γ + ) was significantly increased in pulmonary tissues after HF. In addition, anti-NK1.1 antibodies simultaneously abolished both NK1.1 + cells, including the NK1.1 + NK and NK1.1 + NKT cells in peripheral blood, spleen, and lung tissues, but had no effect on cardiopulmonary structure and function under control conditions. However, systemic inhibition of NK1.1 signaling by anti-NK1.1 antibodies significantly rescued mice from TAC-induced left ventricular inflammation, fibrosis, and failure. Inhibition of NK1.1 signaling also significantly attenuated TAC-induced pulmonary leukocyte infiltration, fibrosis, vessel remodeling, and consequent right ventricular hypertrophy. Moreover, inhibition of NK1.1 signaling significantly reduced TAC-induced pulmonary macrophage and dendritic cell infiltration and activation. Conclusions: Our data suggest that inhibition of NK1.1 signaling is effective in attenuating systolic overload-induced cardiac fibrosis, dysfunction, and consequent pulmonary remodeling in immunocompetent mice through modulating the cardiopulmonary inflammatory response.